RESOURCES PRESENCE ANALYSIS ON SEA TRANSPORTATION POLICY IMPLEMENTATION AT THE RIAU ISLANDS PROVINCE BORDER AREA - Edy Akhyary (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2019)
The Law number 17 year of 2008 becomes an implementing sea transportation guideline and has regulated expressly the transportation activities in ocean, port, safety and shipping securely and the maritime environment protection, recognizes the special sea transportation existence, folk shipping and shipping pioneer. Riau Islands Province which has 2,408 islands and 95.79% sea reaching area also needs a comprehent serious attention. This research aims for analyzing throught the sea transportation policy implementation resources and expected to be able for contributing the various sea transportation problems in several regions, especially in the Riau islands. This study employs a qualitative approach with the research process carried out systematically through in-depth interview operations, observation, literature studies and focus group discussions, studying informaions and analyzing relevantly. The results explain that the sea transportation policy implementation resources also need to get better attention and handling comprehensively.